Pelanggaran Prinsip Kerja Sama dalam Drama “Sweet Home” (스위트홈) - Andriana Dwi Puspita; Young, Hwang Who (Universitas Gadjah Mada, 2023)
This article examines the forms of violation of Grice's maxim of cooperation principles carried out by the characters in the drama Sweet Home (SH) and their relationship with achieving communication goals. This research uses a descriptive-qualitative method referring to Grice's theory of Cooperation Principles (CP) (1975). Research data was obtained using the method of listening without being involved and taking notes. Based on the research results, four forms of single PKS violations were found in SH: the maxims of quantity, quality, relevance, and manner. Apart from these violations, double maxim violations were also found, namely violations of the maxim of relevance and the maxim of manner. The causes of CP violations occur due to the following factors: (1) in the maxim of quantity, the speaker provides excessive information; (2) in the maxim of quality, the speaker conveys incorrect information and uses similes and figures of speech; (3) in the maxim of relevance, the speaker gives information that is implicit and unrelated to the topic of conversation; (4) in the maxim of manner, the speaker sends an ambiguous message, not straightforward and long-winded. This research shows that most conversations that violate the maxim of relevance, the maxim of quality, and the maxim of manner fail to achieve communication goals because the recipient of the message does not understand the message. on the contrary, failure of communication objectives does not occur in a maxim of quantity but only causes ineffectiveness in delivering the message.